Frequency, Clinical Presentation, and Management of Bartholin's Abscess: A Case Study Conducted at Rabia Balkhi Hospital, Afghanistan in 2022 - Hamidi, Hamida (PT. Riset Press International, 2025)
Bartholin's gland abscesses are a relatively common gynaecological condition that can lead to significant discomfort and complications if not managed properly. These abscesses typically result from ductal obstruction or infection of the Bartholin glands, causing localized pain, swelling, and erythema. This study evaluated the incidence, clinical presentation, management strategies, and treatment outcomes of Bartholin's gland abscesses at Rabia Balkhi Hospital, Afghanistan, in 2022. A retrospective cohort study used hospital records of women diagnosed with Bartholin's gland abscesses. Twenty-three cases (n = 23) were identified, representing 0.6% of all gynaecological admissions. The most affected age group was 25-35, accounting for 52% of cases. The most common symptoms included severe localized pain (96%), swelling (87%), and erythema (96%). Incision and drainage were the most commonly performed treatment (74%), followed by marsupialization (17%) and drainage tube insertion (9%). The recurrence rate was 13%, and no significant complications were observed. Statistical analysis showed that the highest incidence was in the 25-35-year age group, with a statistically significant association between age and treatment outcomes (p < 0.05). In conclusion, Bartholin's gland abscesses are relatively rare but more common in women aged 25-35. Incision and drainage remain the most effective treatment, with a low recurrence rate. These findings highlight the importance of early diagnosis and intervention to prevent complications. Further studies with larger sample sizes and longer follow-up periods are needed to refine treatment protocols and minimize recurrence rates.